An Autoethnography of a Doctoral Student’s Identity Development Through Exposure to Short-term Study Abroad. - Cheri L. Hatcher (Adult Education Research Conference, 2024)
This is a reflective autoethnographic study about my short-term study abroad (SSA) experiences as a doctoral student in a US-based adult education program.
Keywords: short-term study abroad; doctoral student identity construction; autoethnography